Analysis of Problems and Legality of Authentic Deed Electronically - Arif Lukman (Sultan Agung Notary Law Review, 2021)
This research discusses the implementation of the regulation of the minister of agrarian and spatial planning (atr)Act No.national land agency (BPN) number 9 of 2019 concerning the implementation of registration of mortgage rights using an electronic system (problematic analysis and validity of authentic deeds electronically). With the background of the Regulation of the Minister of Agrarian and Spatial Planning of the Head of the National Land Agency Number 9 of 2019 concerning Electronic Integrated Mortgage Services which came into effect since it was promulgated, namely on June 21, 2019. This regulation is a continuation of the previous Ministerial Regulation that was passed, namely Permen 3 Act No.2019 concerning the use of electronic systems and Permen 7/2019 regarding changes to the form of certificates. However, the implementation is still not optimal in the field. Therefore, the aim of this research is to analyze the problematics of authentic deeds electronically in relation to the implementation of the regulation of the Minister of ATTAct No.BPN No.9 of 2019 concerning the implementation of registration of mortgage rights with an electronic system. This study uses a normative juridical approach, in addition to using legal principles and principles in reviewing, viewing, analyzing problems. Data collection techniques use books, related constitutions and coupled with field studies. The data from this research were analyzed descriptively qualitatively, by describing all the findings of primary data and secondary data. The results of the analysis are used as material to formulate conclusions in order to answer the problems studied and to formulate suggestions for parties related to this research. The results of this study are The problem of electronic authentic deeds in the implementation of the ministerial regulation ATR Act No. BPN no 9 of 2019 concerning the implementation of registration of mortgage rights with an electronic system, there are two of the most dominant problems, including the Interference of the HT-e System and the Regulations that Have Not Regulated the Subjects and Objects of the Insurance Rights as a whole. Furthermore, on the validity of electronic authentic deeds in the implementation of the regulation of the Minister of ATR Act No. BPN No. 9 of 2019 concerning the implementation of registration of mortgage rights with an electronic system, namely by continuing to implement technological restrictions to maintain the validity of authentic deeds in order to align with the main spirit of the notary profession as a general official.